Numerical Investigation on Fracture Mechanisms and Energy Evolution Characteristics of Columnar Jointed Basalts With Different Model Boundaries and Confining Pressures - Wang, Yongyi; Gong, Bin; Tang, Chun’an (Frontiers in Earth Science, 2021)
To reveal the mechanical mechanisms and energy release characteristics underlying progressive failure of columnar jointed basalts (CJBs) with various model boundaries and confining pressures, by combining the meso-damage mechanics, statistical strength theory, and continuum mechanics, inhomogeneous CJB models with different dip angles to the column axis are constructed. In the cases of plane stress, plane strain, and between plane stress and plane strain, the gradual fracture processes of CJBs are simulated under different confining pressures and the acoustic emission (AE) rules are obtained. The results show that: 1) in the case of plane stress, the fracture process of CJBs along direction I orthogonal to the column axis: at the initial stage of loading, the vertical joints and the transverse joints in the CJB specimen are damaged. Then, more columns in the upper middle part are cracked; 2) in the case between plane stress and plane strain, the fracture process of CJBs along the direction parallel to the column axis: at the initial stage of loading, the columnar joints are damaged. Then, the area of the damaged and broken columns at the top of the specimen increases and the crushing degree intensifies; 3) for the case between plane stress and plane strain, the AE energy accumulation before the peak stress is higher than the plane strain state along the direction orthogonal to the column axis. Meanwhile, along the direction parallel to the column axis, this value becomes larger when changing from the state between plane stress and plane strain to the plane strain state. These achievements will certainly improve our understanding of the fracture mechanism and energy evolution of CJBs and provide valuable insights into the instability precursor of CJBs.